MORAL HAZARD DAN AGENCY COST (Pencederaan Kontrak Bisnis dalam Perspektif Ekonomi Syarî’ah) - wadhan wadhan (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2008)
A contract for business organization or production process may generally involve Principal- agent problems due to information asymetry. Islâmic business contracts has manifold avenues and modalities to be implemented as according to the suitability of time, place and environment.The essential benefits of the Islâmic business contracts is to ensure the benefit of the both partners in the contract. Since the contract for business organization or production process embodies some sort of problems like principal- agent problem due to information asymetry and moral hazard, this also be easily minimised in an Islâmic contract. Therefore, it may  be said that if in an Islâmic economy, Islâmic firm implements  the business contract  as designed and approved by the shariah, then principal- agent problem will be minimised and society  will be more benefited from the welfare motive of the producer and other market agents.